2012
DOI: 10.1259/dmfr/33077422
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial physiological calcifications evaluated with cone beam CT

Abstract: Intracranial physiological calcifications can be a common finding on CBCT scans, whereas pathological intracranial calcifications are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 8 publications
(13 reference statements)
3
37
1
1
Order By: Relevance
“…Further, majority of physiological calcification occurs in a region occupying 12%-66.2% of CP (Daghighi et al 2007;Sedghizadeh et al 2012). We show here that CPC (which is considered as the physiological calcification) was independent of the calcification markers including Ca, vitamin D, and PTH.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Further, majority of physiological calcification occurs in a region occupying 12%-66.2% of CP (Daghighi et al 2007;Sedghizadeh et al 2012). We show here that CPC (which is considered as the physiological calcification) was independent of the calcification markers including Ca, vitamin D, and PTH.…”
Section: Discussionsupporting
confidence: 55%
“…An increase in the plasma concentration of Ca leads to the calcification of soft tissues (Bender 2009), and intracranial physiological calcification frequently occurs (approximately 35.2%) in adults (Sedghizadeh et al 2012). Further, majority of physiological calcification occurs in a region occupying 12%-66.2% of CP (Daghighi et al 2007;Sedghizadeh et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Regrettably, the only descriptions of such findings have been obtained through radiologic studies. 13,15,16,21 A radiographic study of the calcification of the interclinoid and petroclinoid ligaments of the sella turcica in 255 subjects by Cederberg et al 15 found partial calcification of the interclinoid ligament in 39% of the subjects and complete calcification in 8%. The analysis of the pPCL revealed 67% of ligaments with no calcification, 23% with partial calcification, and 9% completely calcified ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…1,12 Ossifications of petroclinoid ligaments are rarely described in anatomical literature, 7,8 with most descriptions of such findings based on radiologic studies. [13][14][15][16] So far, only Kimball et al, 4 Perumal and Gayathri, 11 and Rusu et al 17 have provided observations of ossification of the posterior petroclinoid dural folds on wet specimens. However, these authors focused mainly on the significance of a completely ossified posterior petroclinoid dural fold as a factor potentially relating to trigeminal neuralgia.…”
Section: Introductionmentioning
confidence: 99%
“…6 The consequent need to distinguish clinically important subclinical disease entities having potentially serious medical consequences from benign findings and how to pursue the former has likewise perplexed oral and maxillofacial radiologists; but, unlike the American College of Radiology, the International Association of Dentomaxillofacial Radiology has not yet addressed these issues.…”
mentioning
confidence: 99%